2019
DOI: 10.1007/s11368-019-02302-w
|View full text |Cite
|
Sign up to set email alerts
|

Using spectrocolourimetry to trace sediment source dynamics in coastal catchments draining the main Fukushima radioactive pollution plume (2011–2017)

Abstract: Using spectrocolorimetry to trace sediment source dynamics in coastal catchments draining the 3 main Fukushima radioactive pollution plume (2011-2017) 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Fukushima region over a longer time period (from November 2011 to November 2017) where a mean of 24% (SD, 21%) of the material transiting these systems was modelled to be derived from forested landscapes (Evrard et al, 2019). Cumulatively, these results demonstrate that forested landscapes represent a potential long-term source of particulate contaminated matter that likely will require diligent management for the foreseeable future.…”
Section: Perspectives For Future Researchmentioning
confidence: 85%
See 1 more Smart Citation
“…Fukushima region over a longer time period (from November 2011 to November 2017) where a mean of 24% (SD, 21%) of the material transiting these systems was modelled to be derived from forested landscapes (Evrard et al, 2019). Cumulatively, these results demonstrate that forested landscapes represent a potential long-term source of particulate contaminated matter that likely will require diligent management for the foreseeable future.…”
Section: Perspectives For Future Researchmentioning
confidence: 85%
“…Although this practice has not been specifically investigated in the literature, decontamination of farmland in the Fukushima fallout-impacted region was not limited to the removal of the 5-cm topsoil layer concentrating the radiocesium. After this first step, a layer of crushed granite, extracted from local quarries dedicated to decontamination, is used to replace the removed soil layer (Evrard et al, 2019). The entire soil profile consisting of the residual initial soil (in depth) and this crushed granite layer (on top) is then thoroughly mixed to prepare the soil for recultivation with the objective being to further dilute the residual radiocesium activities in the soil (Figure 3).…”
Section: Soil/farmland Decontaminationmentioning
confidence: 99%
“…In closing, Batista et al (2019) argue that the use of knowledge-based techniques to select fingerprints for modeling will encourage researchers to further develop their understanding of processes that drive erosion and sediment geochemistry across multiple spatial and temporal scales. Evrard et al (2019a) use colorimetric fingerprints to investigate the contribution of different erosion processes to material transiting the Mano and Niida catchments in the Fukushima Prefecture, Japan. The authors demonstrated that erosion processes on cultivated landscapes supplied the majority of sediment (56%) to the river networks followed by subsoil sources (including decontaminated materials-26%) and forest sources (21%).…”
Section: Sediment Source Fingerprinting In the Critical Zonementioning
confidence: 99%
“…In particular, the colorimetric parameters derived from the visible spectrum have been shown to be effective in discriminating sediment sources. Their discrimination power has been tested both individually (Evrard et al, 2019;Martínez-Carreras et al, 2010;Uber et al, 2019) and in combination with other tracers (e.g. geochemical properties (Tiecher et al, 2015)) according to the conventional fingerprinting approach (i.e.…”
Section: Introductionmentioning
confidence: 99%